COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF BROADCASTING MEDIA FIRMS ON INDONESIA STOCK EXCHANGE 2015–2024 - Pratama, Yoga; Sarmigi, Elex (Distribusi - Journal of Management and Business, 2026)
This study aims to analyze and compare the profitability performance of PT Media Nusantara Citra Tbk (MNC), PT Elang Mahkota Teknologi Tbk (EMTEK), and PT Visi Media Asia Tbk (VIVA) over the 2015–2024 period. The urgency of this research is driven by the dynamic media industry, digital transformation, and competition from streaming platforms, which position profitability as a key indicator of business sustainability. This study employs a comparative quantitative approach using secondary data obtained from the companies’ annual reports. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE), and the comparison is tested using the Kruskal-Wallis statistical method. The results indicate that MNC demonstrates the most stable profitability performance despite a decline in the final years, EMTEK shows fluctuating performance with recovery in 2024, while VIVA experiences the highest volatility with dominant negative values and equity risk. The Kruskal-Wallis test reveals significant differences in ROA among the companies, but no significant differences in ROE. Overall, MNC has stronger historical profitability stability compared to EMTEK and VIVA.